An unusual case of right upper quadrant pain in a pregnant woman. Issue 4 (April 2017) - Modayil, Veena; Nelson, Mathew; Stankard, Brendon
Abstract : ABSTRACT: Uterine fibroids occur in up to 30% of women of reproductive age and can cause complications during pregnancy that can harm mother and fetus, such as prematurity and increased risk of miscarriage. This article describes a pregnant woman whose abdominal pain was diagnosed as degenerating uterine fibroids.